Toward intersubjective ethics in community-based research. Issue 4 (7th August 2020) - van Zyl, Izak; Sabiescu, Amalia
ABSTRACT: In this paper, we introduce intersubjective ethics as an approach to ethical practice in community-based research. We argue for the need to think of ethics as an evolving process that is inseparable from the research endeavor, and that dwells on relationships and dialogs among researchers and community members. At the core of our approach is "intersubjectivity" and the related notions of "critical subjectivity" and "critical intersubjectivity"; concepts which are central to participatory inquiry but resonate equally with critical theory and constructivism. The paper describes and exemplifies key characteristics of intersubjective ethics and its relation with research. Furthermore, we introduce key elements that can sensitize the researcher-practitioner to the principles of intersubjective ethics and how to put it in practice in community-based research, by cultivating qualities of self-reflexivity and critical (inter)subjectivity.